Overlapping nuclear import and export paths unveiled by two-colour MINFLUX - Abhishek Sau; Sebastian Schnorrenberg; Ziqiang Huang; Debolina Bandyopadhyay; Ankith Sharma; Clara-Marie Gürth; Sandeep Dave; Siegfried M. Musser (Nature, 2025)
Abstract The nuclear pore complex (NPC) mediates nucleocytoplasmic exchange, catalysing a massive flux of protein and nucleic acid material in both directions1. Distinct trafficking pathways for import and export would be an elegant solution to avoid unproductive collisions and opposing movements. However, the three-dimensional (3D) nanoscale spatiotemporal dynamics of macromolecules traversing the NPC remains challenging to visualize on the timescale of millisecond-scale transport events. Here we used 3D MINFLUX2 to identify the nuclear pore scaffold and then to simultaneously monitor both nuclear import and nuclear export, thereby establishing that both transport processes occur in overlapping regions of the central pore. Whereas translocation-arrested import complexes bound at the pore periphery, tracks of translocating complexes within the central pore region revealed a preference for an approximately 40- to 50-nm diameter annulus with minimal circumferential movement, indicating activity-dependent confinement within the permeability barrier. Movement within the pore was approximately 1,000-fold slower than in solution and was interspersed with pauses, indicating a highly restricted environment with structural constraints and/or transient binding events during transport. These results demonstrate that high spatiotemporal precision with reduced photobleaching is a major advantage of MINFLUX tracking, and that the NPC permeability barrier is divided into annular rings with distinct functional properties.